THE ROLE OF DEFENSE ECONOMIC IN ECONOMIC GROWTH - Saputro, Guntur Eko; Tarigan, Herlina; Rajab, Deni Dadang Ahmad (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
The fundamental problems in economic development in Indonesia are the low level of welfare, unsustainable economic growth, and the inadequate development process of economic sectors. Defense economics is a branch of science that applies economics to national defense issues. Defense economics as a multidisciplinary study discusses resource allocation, income distribution, economic growth, and political stability as applied to topics related to defense. According to the defense economy, the impact of the use of the defense budget on the economy can be viewed from the demand or consumption and supply or production approaches. From the consumption side, the defense can protect national resources against various threats, so that national consumption becomes stable and even increases. This research uses role theory according to Biddle and Thomas, among others, Expectation, Norm, Performance, and Evaluation. The research objective is to provide government input on the importance of the economic role of defense in economic growth in Indonesia. Research using qualitative methods is aimed at understanding social phenomena from the perspective of the participants. The result that has been achieved is that the defense economy plays a role in improving security stability, so it is recommended that the government pay attention to defense-security spending budgeting, in particular the adequacy of its allocation, priority level, and linkages between other components